Increasing Access to Autism Spectrum Disorder Diagnostic Consultation in Rural and Underserved Communities: Streamlined Evaluation Within Primary Care. Issue 1 (January 2020) - Hine, Jeffrey F.; Allin, Jessica; Allman, Angela; Black, Michelle; Browning, Brooke; Ramsey, Bobbie; Swanson, Amy; Warren, Zachary E.; Zawoyski, Andrea; Allen, William
ABSTRACT: Objective: Preliminary feasibility and clinical utility research has demonstrated that implementation of a streamlined diagnostic model embedded within primary care (PC) clinics promotes early identification of young children with autism spectrum disorder (ASD). Use of this model results in dramatically reduced waits for diagnostic consultation, high levels of family/provider satisfaction, and reductions in referrals to overtaxed tertiary diagnostic centers. The current study extends this work by providing data before/after implementation of a streamlined model across a diverse range of PC clinics that provide health care to rural and underserved communities. Methods: The streamlined assessment involved record/history review, diagnostic interview, standard rating scales, and an interactive screening tool. Eighty children between the ages of 19 and 47 months were seen across 5 different clinics. Data were collected through chart review. Results: Implementation of streamlined model resulted in a significant decrease in latency to diagnostic conclusion from a mean of 144.7 to 49.9 days. Children were likely to experience a greater reduction in wait times if they were a PC patient versus a non-PC patient. Conclusion: Results show significant reduction in wait times for ASD diagnostic decisions across both PC and non-PC patients. By reducing waits and identifying concerns more efficiently, we may increase the ability of families to access early intervention and support services.